Sistem Pakar Konseling Siswa SMA Menggunakan Metode Forward Chaining - Juliana Naftali Sitompul; Akim Manaor Hara Pardede; John Darwis Martuadi Saragih (UNIVERSITAS PELITA HARAPAN, 2021)
The age range in Senior High School (SMA) is adolescents, adolescents generally find it difficult to open up to others, and it is also difficult to admit that they need guidance, even teenagers refuse the help adults want to provide. In connection with this, facilities are provided in schools to deal with problem students, in dealing with these problems a special teacher is provided, namely the Guidance and Counseling teacher (CT). Guidance for students is needed in making the right choices or for solving problems faced by humans in everyday life. Guidance must be done through a continuous process because as long as humans live, they definitely need help. With the presence of CT, it does not mean that the school is free from the problem of providing guidance and counseling to students, this is a new problem for schools because it is often found dishonesty or lack of openness of students who have problems in providing information to CT.To overcome the problem of the lack of openness of students in providing information during counseling, in this study a forward chaining method was designed which was implemented into an expert system that could help with problematic student counseling activities, so that using this expert system could assist counseling activities. teachers to facilitate counseling. towards students.